Span-of-control’s role at the intersection of transactional leadership and employee commitment - Tabea R. Mabasa; Chukuakadibia E. Eresia-eke (Acta Commercii)
Orientation: South African state-owned enterprises (SOEs) are overburdened by excessive top-level management, straining human capital budgets. Reducing this may increase the span of control, affecting the relationship between leadership style and employee commitment.